2021
DOI: 10.26434/chemrxiv-2021-g35z0
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and emission properties of 1,1,4,4-tetracyanobutadienes derived from ynamides bearing fluorophores

Abstract: A series of 1,1,4,4-tetracyanobutadienes (TCBD) bearing a large diversity of fluorophores was prepared following a multi-step synthesis. In a crucial last step, all compounds were obtained from the corresponding ynamides which were particularly suitable for the formation of the TCBDs in the presence of tetracyanoethylene via a [2+2] cycloaddition/retroelectrocyclization step (CA-RE). Fluorenyl derivatives including several variations on position 7 and 9, in addition to phenanthrenyl and terphenyl derivatives p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…[47][48][49][50] Therefore, the emission properties of compounds 4 and 13 where examined. While none of them showed a measurable luminescence in dichloromethane, which is in agreement with a previous study on TCBDs derived from ynamides [46] , the tetra-TCBD 4 exhibited a weak luminescence in toluene (quantum yield: 0.6 %). On the contrary, the mono-TCBD 13 did not show any emission in toluene at all.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…[47][48][49][50] Therefore, the emission properties of compounds 4 and 13 where examined. While none of them showed a measurable luminescence in dichloromethane, which is in agreement with a previous study on TCBDs derived from ynamides [46] , the tetra-TCBD 4 exhibited a weak luminescence in toluene (quantum yield: 0.6 %). On the contrary, the mono-TCBD 13 did not show any emission in toluene at all.…”
Section: Resultssupporting
confidence: 92%
“…TCBDs [43,44] have long been thought to be non‐emissive because of fast non‐radiative deactivation pathways [45] . However some groups, including ours, [20,21,46] recently showed that TCBDs could exhibit luminescence, depending on their nature and their environment [47–50] . Therefore, the emission properties of compounds 4 and 13 where examined.…”
Section: Resultsmentioning
confidence: 99%
“…Trolez et al investigated the photoluminescence properties of various fluorophore-containing TCBDs synthesized via reactions between ynamides and TCNE [139]. The study revealed that numerous fluorenyl derivatives and their phenanthrenyl and terphenyl counterparts exhibited noteworthy emission behavior in solid form and in solutions (Figure 6).…”
Section: Photoluminescence Propertiesmentioning
confidence: 99%
“…However, largely, the synthesized 1,1,4,4-tetracyanobuta-1,3-dienes (TCBDs) have been found non-emissive/negligible due to radiation-less decay pathways mediated by photoinduced electron transfer (PET)/twisted intramolecular charge transfer (TICT) phenomena or charge separation [5][6][7][8]. Although emissive TCBD chromophores are rarely reported [9][10][11][12][13][14][15][16], their numerous applications continue to demand their synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain emissive TCBDs, another approach was made by several groups, i.e., fluorophore conjugation with TCBDs, however, only a few reports have successfully shown luminescence behaviour for eg., Trolez and co-workers demonstrated that ynamide-TCBD with fluorophore achieved notable photoluminescence (PL) including NIR emission in an organic apolar solvent, i.e., cyclohexane with a remarkable quantum yield of 7.6% [12,15] and weak NIR emission in the solid-state due to AIE synthon of tetraphenyl ethene (TPE) [16]. Recently, similar TPE-based TCBD derivatives were demonstrated to exhibit photothermal effects [17].…”
Section: Introductionmentioning
confidence: 99%